Lifetime Autler-Townes Splitting of Dressed Multi-Order Fluorescence in Pr3+:YSO - Ali, Imran; Li, Changbiao; Hasan, Abdulkhaleq; Abdisa, Garuma; Liu, Zongchen; Ma, Feng; Zhang, Yanpeng (Frontiers in Physics, 2016)
For first time, we study primary and secondary Autler-Townes (AT) splitting of multi-order fluorescence (FL) in time domain. The AT-splitting of multi-order FL signals are controlled by changing power, detuning, and polarization of single and double dressing in a heteronuclear-like molecule system of Pr+3:YSO. The primary and secondary AT-splitting is caused by double cascaded dressing in time domain. The AT-splitting of multi-order FL in time domain is more sensitive than that of in spectral domain. Such results have potential applications in quantum communication and optical information processing on photonic chip.